Eco-friendly food packaging : young consumers’ perceptions & practices / Norsyamira Shahrin ... [et al.] - Norsyamira, Shahrin; Rabiatul Adawiyah, Abd Rahman; Noorliza, Zainol; Noor Saliza, Salmi; Mohd Faisal, Abdul Wahab (2015)
Despite efforts done by the government which imposes “No Plastic Bag” campaign and a ban on polystyrene foam to pack food, small food businesses, food hawkers and campus cafeteria still fail to play their part fully in this exertion. They continue to sell their foods and drinks using non-biodegradable packaging and likewise, consumer still willingly buys them even though they pose hazard to health and environment. Being a young consumer, university student belongs to a huge group that often buys and consumes takeout food. This research focuses on eco-friendly food packaging based on the perception and the practice of young consumers, in this case the undergraduates of Mara University of Technology (Pulau Pinang) Permatang Pauh Campus. A set of questionnaire was constructed and distributed to 315 respondents using convenient sampling. The collected data were analyzed with simple descriptive statistic of frequency, mean and standard deviation. The result of this study demonstrates that most of the respondents are aware on the subject of ecofriendly food packaging and they are influenced by the factors of advertisement, family and peers. Majority of them also agree that the university should propose some alternative to control and reduce non-biodegradable foods and drinks packaging with the intention to encourage undergraduates to practice the use of eco-friendly food packaging. Despite agreeing that eco-friendly food packaging is important, it is found that the respondents do not actually use or fully practice using ecofriendly food packaging. Majority of them rely on the food sellers to provide the packaging for the food they bought in which most of the sellers apply the conventional food packaging method. Looking into this issue, this situation can be considered disconcerting